Meningkatkan kemampuan motorik kasar anak melalui tari kreasi tradisional mandahiling melayu di taman kanak-kanak al-muhsinin Pasaman barat - Erma Rosdiana (IICET (Indonesian Institute for Counseling, Education and Therapy), 2018)
The level of gross motor skills has not developed, where most children are still shy in moving their bodies, there are still children who are still in place and many irregular children move the body as a whole. The type of research is Classroom Action Research conducted by means of cycles, namely two cycles each cycle of three meetings. The learning outcomes in the initial conditions show that the gross motoric abilities of children have not yet developed and continued improvement in the first cycle through the Mandahiling Malay Traditional Creative Dance activities. In cycle II achieved optimal results with excellent results that Mandahiling Malay traditional creative dance can improve the gross motor skills of children in kindergarten Al-Muhsinin, West Pasaman.